PRIMARY GASTROINTESTINAL STROMAL TUMOUR OF THE PROSTATE: A CASE REPORT OF A RARE TUMOUR - Muhammad Arshad Irshad Khalil; Nouman Khan; Azfar Ali; Khurram Mir (Journal of Cancer and Allied Specialties, 2018)
A 70-year-old gentleman underwent prostatectomy for bladder outlet obstruction due to enlarged prostate and was found to have primary extragastrointestinal stromal tumour (EGIST). He has been started on imatinib therapy and is presently on follow-up. Prostatic EGIST should be one of the differential diagnoses in patients with enlarged prostate with normal prostate-specific antigen levels.